Pengaruh Literasi Ekonomi, Status Sosial Ekonomi, dan Modernitas Terhadap Perilaku Konsumsi Guru Sekolah Dasar di Kecamatan Marioriwawo Kabupaten Soppeng - Febrianty, Mitha Nur; Ahmad, Muh. Ihsan Said; Hasan, Muhammad; Ratna; Tjahyadi, Indra (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2023)
This research is useful for understanding the influence of economic literacy, socioeconomic status, and modernity on the consumption behavior of elementary school teachers in Marioriwawo District, Soppeng Regency. This study uses a type of quantitative research in analyzing the problem in the phenomenon under study. The sample in this study was 81 teachers from a population of 426 teachers who were taken using Simple Random Sampling using the Slovin formula. In analyzing the data, descriptive percentage analysis was used, as well as hypothesis testing. The results of this study show that partially economic literacy (X1), socioeconomic status (X2), modernity (X3) have a positive and significant impact on the consumption behavior of primary school teachers (Y) in Marioriwawo District, Soppeng Regency. In addition, simultaneously economic literacy (X1), socioeconomic status (X2), modernity (X3) together have an effect on the consumption behavior of primary school teachers (Y) in Marioriwawo District, Soppeng Regency.